2018
DOI: 10.17503/agrivita.v40i1.1730
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Tree Height in Estimating Individual Tree Biomass while Considering Errors in Measurements and Allometric Models

Abstract: This study evaluated the uncertainty of individual tree biomass estimated by allometric models by both including and excluding tree height independently. Using two independent sets of measurements on the same trees, the errors in the measurement of diameter at breast height and tree height were quantified, and the uncertainty of individual tree biomass estimation caused by errors in measurement was calculated. For both allometric models, the uncertainties of the individual tree biomass estimation caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…With regard to measurement error and uncertainty, many students were concerned about the estimation of H. Tree height measurements are fraught with error because of the difficulty of seeing the location of the top of the tree (Phalla et al 2018). Thus, there is large uncertainty in the angle from which H is determined.…”
Section: Critical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to measurement error and uncertainty, many students were concerned about the estimation of H. Tree height measurements are fraught with error because of the difficulty of seeing the location of the top of the tree (Phalla et al 2018). Thus, there is large uncertainty in the angle from which H is determined.…”
Section: Critical Discussionmentioning
confidence: 99%
“…Concerned with the H term, students, therefore, considered other approaches such as using sophisticated technologies (e.g., LiDAR), triangulation from the top of a building, and using an allometric equation that does not rely on tree height (cf. Phalla et al 2018).…”
Section: Critical Discussionmentioning
confidence: 99%
“…Many scholars have attempted to model the height-diameter relationship [29,30,[32][33][34][35][36][37] and then estimate stand volume by fitting a related model. Such models can aid in formulating forest management measures [36,38]. The description and explanation of spatial structure and the relationships between single trees have become the focus of forest structure research [8,22] and are receiving increased attention.…”
mentioning
confidence: 99%
“…However, because the variables (DBH, TH) are correlated, the contribution of the correlation was incorporated in the error propagation; thus, the contribution of the uDBH decreased, and consequently the ratio uTH/uDBH favored uTH, having contributions from 37 to 62% to the measurement errors. Chave et al (2004) found also more contribution of the uTH to the measurement error in tropical forest, estimating 48 to 78% form uTH; as well as Phalla et al (2018) who estimated a contribution of 74% from uTH to the measurement errors in evergreen forest.…”
Section: V31 Tree-level (Measurement Contributions)mentioning
confidence: 88%